Strategi Pengelolaan Dan Pengembangan Bumdes Sumber Rejeki Di Desa Sumberporong Kecamatan Lawang - Ana Sopanah; Yuni Kartikasari; Dwi Anggarani (Universitas Musamus,Merauke,Papua, 2021)
Knowing the current condition of the Sumber Rejeki BUMDes, how the Sumber Rejeki BUMDes development strategy is, how to create new strategies to provide solutions to overcome various existing obstacles. This study uses a qualitative approach with an interpretive research design with five informants used. Data collection techniques used in the form of interviews, observation, and documentation. The results of this study indicate that the strategy for developing and managing the Sumber Rejeki BUMDes is by paying attention to the previously determined BUMDes strategy, potential environmental conditions, and strategic plans implemented for future BUMDes and it is necessary to map the BUMDes strategy and then combine it with a new strategy through benchmarking. The choice of strategies that can be chosen by the First Sumber Rejeki BUMDes by maintaining superior products has been carried out since the beginning of the establishment. Second, make strategic innovations that are easy for Sumber Rejeki BUMDes to carry out so that later they can answer the needs of the community. Third, benchmarking or modifying several good BUMDes strategies to be taken while still adjusting to the existing environmental conditions in Sumberporong Village.